2005
DOI: 10.1079/bjn20051456
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns among older Europeans: the EPIC-Elderly study

Abstract: Overall dietary patterns have been associated with health and longevity. We used principal component (PC) and cluster analyses to identify the prevailing dietary patterns of 99 744 participants, aged 60 years or older, living in nine European countries and participating in the European Prospective Investigation into Cancer and Nutrition (EPIC-Elderly cohort) and to examine their socio-demographic and lifestyle correlates. Two PC were identified: PC1 reflects a 'vegetable-based' diet with an emphasis on foods o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
147
3
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(177 citation statements)
references
References 38 publications
23
147
3
4
Order By: Relevance
“…The three dietary patterns identified in the present study were similar to the dietary patterns found by previous studies conducted among Asian and Western populations using factor analysis (10,14,15,22) .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The three dietary patterns identified in the present study were similar to the dietary patterns found by previous studies conducted among Asian and Western populations using factor analysis (10,14,15,22) .…”
Section: Discussionsupporting
confidence: 89%
“…The EPIC-Potsdam study found that physical activity level was positively associated with the 'fruit and vegetable' dietary pattern in men (b 5 0?182) and was negatively associated with the 'bread and sausage' pattern in women (b 5 0?099) (10) . The Multiethnic Cohort Study found that physical activity ($3 times/week) was positively asso- (14) .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with previous studies, we did not find a relation between 'convenience foods' pattern and smoking. In agreement with previous findings, we observed a positive relation between the 'prudent diet' pattern and a high level of physical activity and no smoking (Pryer et al, 2001;Schulze et al, 2001;Tseng and DeVellis, 2001;Costacou et al, 2003;Sanchez-Villegas et al, 2003;Villegas et al, 2004;Bamia et al, 2005;Engeset et al, 2005;Perrin et al, 2005). Although a 'prudent' or 'healthy' pattern has been positively associated with a better health status Schulze and Hoffmann, 2006), unexpected associations were observed between the 'prudent diet' pattern and overweight in women and hyperlipidaemia medication use in men.…”
Section: Discussionsupporting
confidence: 80%
“…Numerous studies have investigated relationships between sociodemographic characteristics, lifestyle and dietary patterns (Whichelow and Prevost, 1996;Greenwood et al, 2000;Pryer et al, 2001;Schulze et al, 2001;Tseng and DeVellis, 2001;Costacou et al, 2003;Sanchez-Villegas et al, 2003;Villegas et al, 2004;Bamia et al, 2005;Engeset et al, 2005;Park et al, 2005;Perrin et al, 2005;Yang et al, 2005;Pala et al, 2006). To our knowledge, only one study investigating the relationship between dietary patterns and their determinants was conducted in France, but among men only (Perrin et al, 2005), and there are no studies that have been carried out among French women and men.…”
Section: Introductionmentioning
confidence: 92%
“…Meat intake has been associated with obesity (27,(32)(33)(34)(35)(36)(37) . However, the present study failed to establish a significant relationship at the 95 % confidence level.…”
Section: Discussionmentioning
confidence: 99%